Genome-Wide Identification, Characterization and Function Analysis of Lineage-Specific Genes in the Tea Plant Camellia sinensis - Zhao, Zhizhu; Ma, Dongna (Frontiers in Genetics, 2021)
Genes that have no homologous sequences with other species are called lineage-specific genes (LSGs), are common in living organisms, and have an important role in the generation of new functions, adaptive evolution and phenotypic alteration of species. Camellia sinensis var. sinensis (CSS) is one of the most widely distributed cultivars for quality green tea production. The rich catechins in tea have antioxidant, free radical elimination, fat loss and cancer prevention potential. To further understand the evolution and utilize the function of LSGs in tea, we performed a comparative genomics approach to identify Camellia-specific genes (CSGs). Our result reveals that 1701 CSGs were identified specific to CSS, accounting for 3.37% of all protein-coding genes. The majority of CSGs (57.08%) were generated by gene duplication, and the time of duplication occurrence coincide with the time of two genome-wide replication (WGD) events that happened in CSS genome. Gene structure analysis revealed that CSGs have shorter gene lengths, fewer exons, higher GC content and higher isoelectric point. Gene expression analysis showed that CSG had more tissue-specific expression compared to evolutionary conserved genes (ECs). Weighted gene co-expression network analysis (WGCNA) showed that 18 CSGs are mainly associated with catechin synthesis-related pathways, including phenylalanine biosynthesis, biosynthesis of amino acids, pentose phosphate pathway, photosynthesis and carbon metabolism. Besides, we found that the expression of three CSGs (CSS0030246, CSS0002298 and CSS0030939) was significantly down-regulated in response to both types of stresses (salt and drought). Our study first systematically identified LSGs in CSS, and comprehensively analyzed the features and potential functions of CSGs. We also identified key candidate genes, which will provide valuable assistance for further studies on catechin synthesis and provide a molecular basis for the excavation of excellent germplasm resources.